Do plant‐ and soil‐mediated legacy effects impact future biotic interactions?. (18th May 2015) - Wurst, Susanne; Ohgushi, Takayuki
Summary: Biotic interactions of plants can have legacy effects mediated by changes in plant traits and soil characteristics. Legacy effects are defined as effects that persist after the causal biotic interaction ceases, because plant traits and soil characteristics are plastic and modifications may be maintained for long time periods. To date, studies on biotic interactions of plants with above‐ and below‐ground organisms and their plant‐mediated interactions have mainly focused on short‐term effects in the continuous presence of interacting organisms. Little is known about how long the changes in plant traits and soil characteristics persist after the biotic interaction ceases and indirectly affect future biotic interactions and community assembly. Further, since some organisms switch between above‐ and below‐ground compartments during ontogeny, impacts on soil‐dwelling larval stages can have direct legacy effects on their above‐ground adult stages and vice versa. Elucidating legacy effects of biotic interactions above and below the ground will provide a deeper insight into a better understanding of the importance of plant trait‐ and soil characteristic‐mediated indirect interactions in shaping community assembly, biodiversity and ecosystem function. Abstract : Lay Summary